Congruences on nilpotent-generated partial transformation semigroups - Smith, M. Paula Marques (2009)
In 1987, Sullivan characterised the elements of the semigroup NP(X ) generated by the nilpotents in P(X ), the semigroup (under composition) consisting of all partial transformations of a set X . In 1999, Marques-Smith and Sullivan determined all the ideals of NP(X ) for arbitrary X . In this paper, we use that work to describe all the congruences on NP(X ).